Perbandingan komposisi spesies ikan di kawasan Air Keruh (Brown Water) dan Air Hitam (Blackwater) di Batang Kerang, dan Balai Ringin, Serian - Anderson Jawi, Ak. Esa. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Comparison of fish composition between brown and blackwater of Batang Kerang was carried out during rainy season (Sept. 2004) and during dry season (Jan. 2005). Thirty six species belonging to 14 families was collected in both brown and black water. Thirty two species belonging to 12 families was found in brown water and 12 species belonging to seven families was found in black water. Brown water area was dominated by Cyprinidae (63.82 %) while the blackwater area dominated by Helostomatidae (59.8 %). There are significant different in water quality observed between brown and blackwater. Water qualities are relatively low in both area and seasonal factor affected water quality in Batang Kerang.